Dousing the flame: reviewing the mechanisms of inflammatory programming during stress-induced intrauterine growth restriction and the potential for ω-3 polyunsaturated fatty acid intervention - White, Melanie R.; Yates, Dustin T. (Frontiers in Physiology, 2023)
Intrauterine growth restriction (IUGR) arises when maternal stressors coincide with peak placental development, leading to placental insufficiency. When the expanding nutrient demands of the growing fetus subsequently exceed the capacity of the stunted placenta, fetal hypoxemia and hypoglycemia result. Poor fetal nutrient status stimulates greater release of inflammatory cytokines and catecholamines, which in turn lead to thrifty growth and metabolic programming that benefits fetal survival but is maladaptive after birth. Specifically, some IUGR fetal tissues develop enriched expression of inflammatory cytokine receptors and other signaling cascade components, which increases inflammatory sensitivity even when circulating inflammatory cytokines are no longer elevated after birth. Recent evidence indicates that greater inflammatory tone contributes to deficits in skeletal muscle growth and metabolism that are characteristic of IUGR offspring. These deficits underlie the metabolic dysfunction that markedly increases risk for metabolic diseases in IUGR-born individuals. The same programming mechanisms yield reduced metabolic efficiency, poor body composition, and inferior carcass quality in IUGR-born livestock. The ω-3 polyunsaturated fatty acids (PUFA) are diet-derived nutraceuticals with anti-inflammatory effects that have been used to improve conditions of chronic systemic inflammation, including intrauterine stress. In this review, we highlight the role of sustained systemic inflammation in the development of IUGR pathologies. We then discuss the potential for ω-3 PUFA supplementation to improve inflammation-mediated growth and metabolic deficits in IUGR offspring, along with potential barriers that must be considered when developing a supplementation strategy.